2020
DOI: 10.1177/0748233720936825
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcium and EDTA on copper ion bioavailability in copper nanoparticle toxicity tests improves understanding of nano-specific effects

Abstract: Metal-based nanoparticles (NPs) can release metal ions that are toxic to aquatic organisms; however, whether the toxicity is from metal ions rather than unique “nano-scale” effects of the NPs is unresolved. The present study aimed to compare the toxicity of Cu2+ and Cu-NPs in larval zebrafish ( Danio rerio) to clarify whether toxic effects are attributable to release of Cu ions and to determine the effect of the chelating agent ethylenediaminetetraacetic acid (EDTA) and calcium hardness (as CaCO3) on the Cu to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…31−37 And Mt2 was downregulated in the EaCpG + radiotherapy treatment, indicating that EaCpG + radiotherapy treatment inhibited tumor cell migration. 38 Also, both EaCpG and the combination of radiotherapy + EaCpG increased the expression of Tnf, Tlr9, and Tlr1 compared to other treatments (Figure S17). Meanwhile, we found that radiotherapy alone led to positive regulation of programmed cell death, the intrinsic apoptotic signaling pathway (Figure S18), Afterward, we performed enrichment analysis of gene ontology (GO) and KEGG using Metascape, which revealed that EaCpG enhanced the pattern recognition receptor signaling pathway compared to pCpG treatment (Figure 4H, left panel).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…31−37 And Mt2 was downregulated in the EaCpG + radiotherapy treatment, indicating that EaCpG + radiotherapy treatment inhibited tumor cell migration. 38 Also, both EaCpG and the combination of radiotherapy + EaCpG increased the expression of Tnf, Tlr9, and Tlr1 compared to other treatments (Figure S17). Meanwhile, we found that radiotherapy alone led to positive regulation of programmed cell death, the intrinsic apoptotic signaling pathway (Figure S18), Afterward, we performed enrichment analysis of gene ontology (GO) and KEGG using Metascape, which revealed that EaCpG enhanced the pattern recognition receptor signaling pathway compared to pCpG treatment (Figure 4H, left panel).…”
Section: Resultsmentioning
confidence: 92%
“…Notably, EaCpG treatment increased the expressions of some interferon response genes such as Irf7, Oas2, Oas3, SIfn2, SIfn4, and SIfn8 (Figure F) compared to pCpG treatment. Ly6c2 (lymphocyte antigen 6 complex, locus2) and Cxcl10, the indicatives of immunotherapy response, were upregulated in EaCpG compared to pCpG. EaCpG + radiotherapy treatment increased Fcrl5, Evi2b, Cd300e, Camk1d, Aif1, Bcl11b, and Traf3ip3 compared to pCpG + radiotherapy (Figure G), which are typically associated with innate immune activation, positive regulation of NK cell and neutrophil differentiation, and macrophage and T-lymphocyte activation. And Mt2 was downregulated in the EaCpG + radiotherapy treatment, indicating that EaCpG + radiotherapy treatment inhibited tumor cell migration . Also, both EaCpG and the combination of radiotherapy + EaCpG increased the expression of Tnf, Tlr9, and Tlr1 compared to other treatments (Figure S17).…”
Section: Resultsmentioning
confidence: 99%
“…Detoxification of cadmium with EDTA has been shown to be therapeutically beneficial in humans and animals when done using established protocols. EDTA was found to decrease Cu toxicity in freshwater fish [ 17 ]. Moreover, application of EDTA to the Cd-treated seedlings reduces Cd-induced oxidative injuries by restricting Cd uptake; increasing nonprotein thiols concentration and upregulating most of the components of their antioxidant defense and glyoxalase systems [ 18 ].…”
Section: Introductionmentioning
confidence: 99%